Dust Emission Investigation of Agricultural Powdered Materials. Issue 1 (1st May 2022) - Rani, S.I.; Azhar, N.A.L.; Abdullah, A.H.; Daud, M.A.A.; Mohamed, A.
Abstract: The dust emission in the workplace may affect workers health or create safety problem. This paper describes the development of an experimental apparatus to investigate dust emission as a function of particle size in various fall distances and different conveying velocity. For this purpose, four types of agricultural dusts (castor sugar, oat, semolina and tea powder) were used. It is found that the particle properties and fall distance have strong influence on the amount of dust emission generated. The result reveal that tea powder produced highest amount of dust emission (< 211 μm) in all fall distance during flow fall process. Finding from this work is useful to understand the mechanism and risk of dust emission in agricultural activities.